Politik Ekonomi Dalam Kebijakan Pengelolaan Parkir Pada Minimarket Di Kecamatan Rawalumbu Kota Bekasi - Sitorus, Daniel Maranata; Noak, Piers Andreas; Apriani, Kadek Dwita (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
Research tried to find out the subject matter in the parking policy at the minimarket in 2019 and knew the plans of Bapenda and Dishub after temporarily dismissing the parking policy. The study used the theory of State and Illegality Edward Aspinall &van Klinken. Research methods are used in the form of qualitative research types with data search through observation, interviews, and documentation. The results of this study are first, the Bekasi City Government wants to take advantage of the tax potential that can be obtained from parking in the minimarket, because it can be used as an opinion for the Bekasi City area. Second, in 2019 Bapenda engaged the organization to be the party that manages parking in the minimarket because to realize the vision-mission of the Mayor of Bekasi itself, one of the visions that Bapenda wants to realize is to create the widest range of jobs. Third, Bapenda and Dishub are currently conducting a review of the parking policy in the minimarket which has been temporarily stopped after problems between the minimarket and the organization in 2019. Bapenda and Dishub are planning to make a policy of paying contributions to parking at minimarkets. The contribution payment policy that is being designed as a form of seriousness of the Bekasi City Government in the desire to use parking in the potentially taxable minimarket.